1996
DOI: 10.1128/jb.178.23.6810-6816.1996
|View full text |Cite
|
Sign up to set email alerts
|

The glutamic acid residue at amino acid 261 of the alpha subunit is a determinant of the intrinsic efficiency of RNA polymerase at the metE core promoter in Escherichia coli

Abstract: A mutation in the rpoA gene (which encodes the ␣ subunit of RNA polymerase) that changed the glutamic acid codon at position 261 to a lysine codon decreased the level of expression of a metE-lacZ fusion 10-fold; this decrease was independent of the MetR-mediated activation of metE-lacZ. Glutamine and alanine substitutions at this position are also metE-lacZ down mutations, suggesting that the glutamic acid residue at position 261 is essential for metE expression. In vitro transcription assays with RNA polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…UP elements are present in promoters transcribing rRNAs, tRNAs, and mRNAs, and good proximal subsites are more frequent than good distal subsites or good full UP elements in E. coli promoters (Estrem et al 1999). In this regard, it has been reported that substitutions for E261 reduce factor-independent transcription from the metE promoter in vitro and in vivo (Jafri et al 1995(Jafri et al , 1996. The same ␣CTD-interaction that facilitates UP element proximal subsite function apparently also plays a role in activation by transcription factors at Class I promoters, where ␣CTD is at the same position relative to as at promoters with proximal subsites (Busby and Ebright 1999).…”
Section: ␣Ctd-interactions At Other Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…UP elements are present in promoters transcribing rRNAs, tRNAs, and mRNAs, and good proximal subsites are more frequent than good distal subsites or good full UP elements in E. coli promoters (Estrem et al 1999). In this regard, it has been reported that substitutions for E261 reduce factor-independent transcription from the metE promoter in vitro and in vivo (Jafri et al 1995(Jafri et al , 1996. The same ␣CTD-interaction that facilitates UP element proximal subsite function apparently also plays a role in activation by transcription factors at Class I promoters, where ␣CTD is at the same position relative to as at promoters with proximal subsites (Busby and Ebright 1999).…”
Section: ␣Ctd-interactions At Other Promotersmentioning
confidence: 99%
“…␣ E261A reduces Class I CRP-dependent activation of the lac promoter Savery et al 2002) and Class I TyrR-dependent activation of the mtr promoter (Yang et al 1997). E. coli strains haploid for E261K also display a variety of other phenotypes (Jafri et al 1995(Jafri et al , 1996, suggesting that this surface on ␣CTD plays a role in multiple cell functions.…”
Section: ␣Ctd-interactions At Other Promotersmentioning
confidence: 99%
“…To determine whether the Strep-tagged ␣ is also functional, we tested for the ability of Strep-tagged ␣ to complement a known rpoA mutant in vivo. The mutant strain GS1040 carries the chromosomal E261K rpoA allele, which prevents growth on glucose minimal medium (16). Transformants of GS1040 carrying the pREII-Strep␣ plasmid exhibit growth on glucose minimal medium indistinguishable from that of the wild-type strain (GS162) or from that of transformants of GS1040 carrying pREII␣, suggesting that Streptagged ␣ is incorporated into RNAP and that the Strep tag does not interfere with function.…”
Section: Gs162mentioning
confidence: 99%
“…Aliquots of reconstituted core RNAP were incubated in the presence of a 1.5 molar excess of purified 70 subunit to ensure the formation of RNAP holoenzyme for use in single-round runoff transcription assays in the presence of heparin as previously described (16). The activity of each reconstituted RNAP was normalized based on the amounts of lacUV5 and RNA-I transcripts produced when the supercoiled plasmid pRLG593 was used as the template (35).…”
Section: Methodsmentioning
confidence: 99%